Design and control of the rapid legged platform GAZELLE. (April 2020) - Jeong, Hyobin; Lee, KangKyu; Kim, Wooshik; Lee, Inho; Oh, Jun-Ho
Abstract: This study presents the design and system integration of the 13-degree-of-freedom legged platform, GAZELLE. The goal of this research is to develop a fast and reliable biped platform for walking experiments. Rapid leg movement can increase robustness in walking stability. During external push or walking on uneven ground, fast leg movement can realize an abrupt change on the landing position. GAZELLE is characterized by a lightweight design, a link-driven structure for low leg inertia, a wide range of motion, and a direct-stacked fin air-cooling module. The actuator is designed using a special type of harmonic drive (lightweight CSF type) and a 200 W brushless DC motor with high power density. The knee and ankle joints are link-driven; hence, the actuators can be placed on the upper position, and the leg inertia is reduced. A novel air cooler design for the cylinder-type motor, which is extremely light and highly efficient, is introduced herein and realized by stacking cooling fins to the motor housing. This study also includes a brief introduction of a stabilizing controller and the walking experiment results of GAZELLE.